HUBUNGAN KARAKTERISTIK REMAJA DENGAN KEJADIAN KECELAKAAN LALU LINTAS PADA KOMUNITAS MOTOR SULUT KING COMMUNITY (SKC) MANADO - Ratnasari, Fitria; Kumaat, Lucky T.; Mulyadi, Ns (Universitas Sam Ratulangi, 2014)
Abstract: Traffic accidents are one of the public health problem that affects all sectors of life. Traffic accidents involving adolescents is relatively large. This happens because the majority of traffic offenders who tend to reckless street are adolescent and young persons. The purpose of this research to identify the relationship between the characteristics of adolescents with an incidence of traffic accidents in the motorcycle community SULUT King Community (SKC). The characteristics of adolescents are adolescents age, adolescents sex, education level, adolescents socioeconomic, time, and the rate of speed. The design of this research is the retrospective design. The research fulfiled was conducted on September 2014 in the motorcycle community Wanea Secretariat SULUT King Community (SKC) Manado with 45 sample. The result of this research were calculated using Chi-square test and the results showed that there was no relationship between adolescents age with an incidence of traffic accidents, p = 0.650. There is a relationship between adolescents sex with an incidence of traffic accidents, p = 0.016. There is no relationship between the education level with an incidence of traffic accidents, p = 1.000. There is a relationship between adolescents socioeconomic with an incidence of traffic accidents, p = 0.013. There is a relationship between time with an incidence of traffic accidents, p = 0.001. There is a relationship between the rate of speed with an incidence of traffic accidents, p = 0.000. The suggestion for adolescents be able to understand about traffic accidents, and whatever may be the cause of traffic accidents. Key Word : Characteristics, Traffic Accidents. Bibliography : 24 (2007-2014). Abstrak: Kecelakaan lalu lintas merupakan salah satu masalah kesehatan masyarakat yang mempengaruhi semua sektor kehidupan. Kecelakaan lalu lintas melibatkan anak remaja tergolong besar. Hal ini terjadi karena mayoritas para pelanggar lalu lintas yang cenderung ugal-ugalan dijalan adalah oknum remaja dan pemuda. Tujuan penelitian untuk mengidentifikasi hubungan antara karakteristik remaja dengan kejadian kecelakaan lalu lintas pada komunitas motor SULUT King Community (SKC). Karakteristik remaja yang diteliti tersebut antara lain adalah usia remaja, jenis kelamin remaja, tingkat pendidikan, sosial ekonomi remaja, waktu, dan tingkat kecepatan. Desain penelitian ini adalah desain retrospektif. Penelitian dilaksanakan pada bulan september 2014 di Wanea Sekretariat Komunitas Motor Sulut King Community (SKC) Manado dengan 45 sampel. Hasil penelitian dihitung dengan menggunakan Uji Chi-square pada tingkat kemaknaan 95% () dan hasil menunjukkan bahwa tidak ada hubungan antara usia remaja dengan kejadian kecelakaan lalu lintas, p = 0,650. Ada hubungan antara jenis kelamin remaja dengan kejadian kecelakaan lalu lintas, p = 0,016. Tidak ada hubungan antara tingkat pendidikan dengan kejadian kecelakaan lalu lintas, p = 1,000. Ada hubungan antara sosial ekonomi remaja dengan kejadian kecelakaan lalu lintas, p = 0,013. Ada hubungan antara waktu dengan kejadian kecelakaan lalu lintas, p = 0,001. Ada hubungan antara tingkat kecepatan dengan kejadian kecelakaan lalu lintas, p = 0,000. Saran bagi remaja agar dapat memahami tentang kecelakaan lalu lintas dan apa saja yang mungkin menjadi penyebab terjadinya kecelakaan lalu lintas. Kata Kunci : Karakteristik, Kecelakaan Lalu Lintas. Daftar Pustaka : 24 (2007-2014).